Exosome Shedding Is Concordant with Objective Treatment Response Rate and Stratifies Time to Progression in Treatment Naïve, Non-Resectable Hepatocellular Carcinoma - Kelley G. Núñez; Dorota Wyczechowska; Mina Hibino; Tyler Sandow; Juan Gimenez; Ali R. Koksal; Yucel Aydin; Srikanta Dash; Ari J. Cohen; Paul T. Thevenot (Livers, 2023)
Translational strategies to characterize and monitor extracellular vesicles such as exosome (EX) shedding and the clinical impact of this data within hepatocellular carcinoma (HCC) remains unclear. In this study, EX shedding was assessed in early-stage HCC and evaluated as a stratification factor for time to progression (TTP) following first-cycle liver-directed therapy (LDT). Plasma EXs were isolated from HCC patients undergoing LDT using ultracentrifugation. Purified EXs were stained using markers CD9 and CD63 and quantified using an ImageStreamX flow cytometer. Circulating EXs expressing CD9 were isolated at 10-fold higher levels compared to CD63. The intensity of CD9+ EX shedding following LDT was positively correlated with treatment response. High post-LDT CD9+ EX shedding stratified TTP risk with a 30% lower frequency of disease progression at 1 year following LDT. Post-LDT high CD9+ EX shedding was observed in 100% (10/10) of patients successfully bridged to liver transplantation while only 22% (2/9) of patients with tumor progression had high CD9+ EX shedding post-LDT. CD9+ EX shedding also stratified TTP risk within the first cycle objective response rate (ORR) group, identifying patients still at higher disease progression. EX shedding was concordant with imaging response rate, stratified TTP in early-stage HCC, and may have important implications for assessing post-LDT viable, biologically aggressive HCC.